Shaping the future of Uzbekistan’s tourism: An in-depth analysis of infrastructure influence and strategic planning - Arabov, Nurali; Nasimov, Dilmurod; Janzakov, Bekzot; Khomitov, Komiljon; Utemuratova, Gulnarakhan; Abduraimov, Dilshod; Ismailov, Baxit (Journal of Eastern European and Central Asian Research (JEECAR), 2024)
This article presents a comprehensive assessment of the impact of infrastructure on tourism, exploring its crucial role in shaping the tourism industry. Through expert methods and survey analysis, the study highlights the quality of infrastructure by assessing the development level of transportation, accommodation, tourist attractions, amenities, and tourism services in Uzbekistan’s 14 regions. As a result, the classification of regions with regard to infrastructure development is proposed. In addition, an equilibrium equation in the tourism market concerning infrastructure facilities is suggested, which can be used to assess the balanced development of general infrastructure. The findings underscore the need for policymakers and stakeholders to recognize the direct correlation between infrastructure and tourism success, providing insights to guide future infrastructure planning and development initiatives in the ever-evolving global tourism landscape.